(untitled) (Baghdad Science Journal, 2019)
The present study aimed to investigate the histological changes of heart, lung, liver and kidney which caused by different concentrations (10, 20 and 40 mg/kg) of Ivabradine. Results of the study revealed some histological changes represented by aggregation of the lymphocytes around respiratory bronchioles of the lung. In the liver, the drug caused hepatocyte necrosis and infiltration of the lymphocytes. In Kidney, there are no histopathological modifications in the tissue after the animals treated with 10 mgof Ivabradine. When the animals treated with Ivabradine drug at 20mg/kg of bw, dose showed vascular congestion between myocardial fibers of heart. Emphysematous changes of the alveoli and infiltration of lymphocytes around respiratory bronchioles of lung. In the liver there were dilated blood sinusoids. Also, there are vascular congestion and congestion of capillaries in the glomerular of kidney. Male mice treated with Ivabradine drug at 40 mg/kg of bw cause increase spaces between myocardial fibers, cardiac atrophy and myocardial degeneration in the heart. In addition, there are infiltration of lymphocytes around respiratory bronchioles, pulmonary congestion and emphysematous changes of the alveoli in lung. In the liver, the drug cause amyloid deposition and degeneration of hepatocytes. Furthermore, the drug caused vascular congestion in the kidney. Conclusion: From the current study, we conclude that the different concentrations of Ivabradine caused tissue changes in the heart, lung, liver and kidneys. The study should continue using different drugs and concentrations.